TOPOLOGY UNVEILED: UNDERSTANDING CONTINUOUS FUNCTIONS AND THEIR ROLE IN COMPUTATIONAL MATHEMATICS - NALINI, Dr. M. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
The field of computational mathematics relies heavily on the principles of topology, especially the concept of continuous functions. This research article delves into the fundamentals of topology and explores the crucial role that continuous functions play in computational mathematics. By unraveling the theoretical foundations and practical applications, we aim to provide a comprehensive understanding of how topology contributes to the advancement of computational methods.